SAINS AKUNTANSI CINTA : PENDEKATAN DIALOGIS PADA MAHASISWA AKUNTANSI - Wiwit Hariyanto; Ruci Arizanda R; Lailul Mursyidah (Universitas Nahdlatul Ulama Sidoarjo, 2021)
This study aims to find out how to build accounting knowledge through a process of thought, experience and reflection with love for students of the Accounting Study Program, Faculty of Economics and Business, University of Muhammadiyah Sidoarjo. This research is a qualitative research. The objects of this research are Accounting Students and Accounting Study Program Lecturers. Data collection techniques in this study by conducting interviews, observation and documentation. Test the validity of the data using the Source Triangulation Technique. The conclusion of this study is that building accounting knowledge through the process of thinking, experience, and contemplation with love will give real meaning. Through the thought process, students can develop theory or practice of accounting science. From the thought process, students gain experience as knowledge, learning, and decision making. While the process of contemplation as awareness in achieving success. Universal love is not only for fellow living beings, but for all aspects of life and God acts as a fortress of the hearts of students of an accountant profession who work sincerely so that the accounting knowledge obtained is useful and gets blessings in life.